Refining DNA barcoding coupled high resolution melting for discrimination of 12 closely related croton species - Maslin Osathanunkul (2018)
© 2015 Osathanunkul et al. This is an open access article distributed under the terms of the Creative Commons Attribut ion License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. DNA barcoding coupled high resolution melting (Bar-HRM) is an emerging method for species discrimination based on DNA dissociation kinetics. The aim of this work was to evaluate the suitability of different primer sets, derived from selected DNA regions, for Bar-HRM analysis of species in Croton (Euphorbiaceae), one of the largest genera of plants with over 1,200 species. Seven primer pairs were evaluated (matK, rbcL1, rbcL2, rbcL3, rpoC, trnL and ITS1) from four plastid regions, matK, rbcL, rpoC, and trnL, and the nuclear ribosomal marker ITS1. The primer pair derived from the ITS1 region was the single most effective region for the identification of the tested species, whereas the rbcL1 primer pair gave the lowest resolution. It was observed that the ITS1 barcode was the most useful DNA barcoding region overall for species discrimination out of all of the regions and primers assessed. Our Bar-HRM results here also provide further support for the hypothesis that both sequence and base composition affect DNA duplex stability.